Uranium and technetium interactions with wüstite [Fe1–xO] and portlandite [Ca(OH)2] surfaces under geological disposal facility conditions. (October 2014) - Van Veelen, A.; Preedy, O.; Qi, J.; Law, G. T. W.; Morris, K.; Mosselmans, J. F. W.; Ryan, M. P.; Evans, N. D. M.; Wogelius, R. A.
Abstract: Iron oxides resulting from the corrosion of large quantities of steel that are planned to be installed throughout a deep geological disposal facility (GDF) are expected to be one of the key surfaces of interest for controlling radionuclide behaviour under disposal conditions. Over the lengthy timescales associated with a GDF, the system is expected to become anoxic so that reduced Fe(II) phases will dominate. Batch experiments have therefore been completed in order to investigate how a model reduced Fe-oxide surface (wüstite, Fe1–x O) alters as a function of exposure to aqueous solutions with compositions representative of conditions expected within a GDF. Additional experiments were performed to constrain the effect that highly alkaline solutions (up to pH 13) have on the adsorption behaviour of the uranyl (UO2 2+ ) ion onto the surfaces of both wüstite and portlandite [Ca(OH)2 ; representative of the expected cementitious phases]. Surface co-ordination chemistry and speciation were determined by ex situ X-ray absorption spectroscopy measurements (both X-ray absorption near-edge structure analysis (XANES) and extended X-ray absorption fine structure analysis (EXAFS)). Diffraction, elemental analysis and XANES showed that the bulk solid composition and Fe oxidation state remained relatively unaltered over the time frame of these experiments (120 h), although under alkaline conditions possible surface hydroxylation is observed, due presumably to the formation of surface hydroxyl complexes. The surface morphology, however, is altered significantly with a large degree of roughening and an observed decrease in the average particle size. Reduction of U(VI) to U(IV) occurs during adsorption in almost all cases and this is interpreted to indicate that wüstite may be an effective reductant of U during surface adsorption. This work also shows that increasing the carbonate concentration in reactant solutions dramatically decreases the adsorption coefficients for U on both wüstite and portlandite, consistent with U speciation and surface reactivity determined in other studies. Finally, the EXAFS results include new details about exactly how U bonds to this metal oxide surface.